Bimbingan Islami dalam Mengatasi Perilaku Bully - Nova Syahreny; Samsuar; Rizky Andana Pohan (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2020)
Bullying is a behavior of intolerance to differences and freedom. In Islam, it is strictly forbidden and strongly discourages the condescension of others. Islamic Guidance is the activity of providing assistance to individuals and groups continuously and systematically to solve problems in his life in accordance with the provisions of Allah SWT which is guided by the Qur'an and Hadith, so that they can achieve happiness later. Islamic guidance is very important in dealing with bullying that occurs to create quality students. This type of research is qualitative research, research data sources are classified as primary data and secondary data. Data collection tools and techniques used were interview, observation and documentation. The results showed that Islamic guidance for students in the Tazkiah Langsa Integrated Islamic Elementary School, was a systematic assistance in solving problems surrounding bully behavior in schools.